Hubungan Perilaku Konsumsi Tuak dan Merokok dengan Tekanan Darah Lansia - Dion Vandy Santos Hutasoit; Alam Bakti; Lita Sri Andayani; Namora Lumongga Lubis (Madani: Jurnal Ilmiah Multidisiplin, 2026)
Hypertension was one of the most common health problems among older adults and could be influenced by various behavioral factors, including palm wine (tuak) consumption and smoking habits. This study aimed to determine the relationship between palm wine consumption behavior and smoking habits with blood pressure among older adults. An analytical survey with a cross-sectional design was conducted in Bakal Julu Village, Dairi Regency, in 2026. The study population consisted of 66 older adults aged 60 years and above, and all eligible participants were selected using the total sampling technique. Data were collected through interviews using questionnaires and blood pressure measurements. The data were analyzed using the Chi-Square test with a 95% confidence level. The results showed that there was a significant relationship between palm wine consumption behavior and blood pressure among older adults (p=0.014). In addition, smoking habits were significantly associated with blood pressure among older adults (p=0.001). The findings indicated that older adults with higher levels of palm wine consumption and smoking habits tended to have a higher prevalence of elevated blood pressure. It was concluded that palm wine consumption behavior and smoking habits were significantly related to blood pressure among older adults.